The Student’s Ability in Using Punctuation and Capitalization through Performing Habit of Writing Diary - Nurhayati, Siti (INTERACTION: Jurnal Pendidikan Bahasa, 2019)
In this study, the writer chose the students ability in using punctuation and capitalization through performing habit of writing diary at the second grade of SMP GUPPI Salawati. For that reason the writer wants to investigate and doing research in the library. The formulation of problem in this research are How is the students competence in apply writing mechanism, and what is the effect of performing habit of writing diary to increase students skill in writing mechanism. The methodology of this study is experimental study. it is means that its need statistic approach to explore the material. There are some of technique of collecting data such as the researcher after developing the test as the instrument of the research, asked the sample (students) to complete the text with punctuation, After they handed their works the writer checked the punctuation they had applied in the given text, and the writer analyze the comments or the mistake they made based on the theory. The result of this study is the writer found that teaching writing mechanism by performing habit of writing diary better than without performing habit of writing diary. It means that the students are more interest to write with writing diary and without writing diary.